STRATEGI PROMOSI AGROEDUKASI PADA PT. TANIKOTA AGRIBUDAYA EDULESTARI - Risda Anastasia; Lucyana Trimo (Universitas Galuh, 2023)
PT. Tanikota Agribudaya Edulestari is an agroeducation company. All this time, Tanikota has executed some promotion strategies that have attracted many visitors. However, Covid-19 requires that activities in Tanikota be stopped for a while. Likewise with promotion activities that don’t have innovation and depend on word of mouth. So, when Tanikota is reopened, the number of visitors doesn’t increase significantly. This study aims to (1) Analyze Tanikota promotion before and during Covid-19 pandemic (2) Identify internal and external factors at Tanikota (3) Formulate priority of promotion strategy for Tanikota. The design used in this study is qualitative with case study research technique. The first objective was analyzed using descriptive analysis and the second objective was analyzed using Analytical Hierarchy Process. The result of the study showed that before pandemic, Tanikota executed some promotion strategies such as personal selling, word of mouth, sales promotion, publicity, instruction materials, corporate design and social media marketing, whereas during pandemic, Tanikota depends more on word of mouth. In addition, there are 8 strengths, 10 weaknesses, 9 opportunities, 6 threats in Tanikota and the main priority of the promotion strategy is optimizing social media with a weight of 0,206.